2019
DOI: 10.17140/poj-3-110
|View full text |Cite
|
Sign up to set email alerts
|

The Evolving Field of Stereotactic Body Radiation Therapy in Pancreatic Cancer

Abstract: Pancreatic cancer remains a devastating disease with dismal outcomes despite the development of novel chemotherapeutic regimens and radiation techniques. Stereotactic body radiation therapy (SBRT) offers an advantage both in image guidance and radiation dose delivery to direct ablative doses to tumors with acceptable toxicity compared to conventional techniques. Recent literature is clustered with data pertaining to SBRT in patients with resectable, borderline resectable and locally advanced pancreatic tumors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…SBRT is a new development in the field of radiotherapy. 43 By applying image guidance, the tumor can be followed during the radiation (tracking), or radiation can be interrupted when the tumor moves out of the beam (gating). This allows high doses of radiation in a very short period of time with less toxicity than conventional chemoradiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…SBRT is a new development in the field of radiotherapy. 43 By applying image guidance, the tumor can be followed during the radiation (tracking), or radiation can be interrupted when the tumor moves out of the beam (gating). This allows high doses of radiation in a very short period of time with less toxicity than conventional chemoradiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…125 I seeds can continuously release a low dose of γ-ray when they are implanted into tumor tissue. It can damage the DNA of tumor cells and induce apoptosis of tumor cells, so as to kill the proliferative cancer cells[ 17 , 18 ]. The advantages of 125 I seeds in the treatment of pancreatic cancer are local adaptation and low dose continuous therapy[ 19 - 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…24 A previous NCDB analysis (data from 1998-2012) demonstrated that SBRT was associated with a 1.4-month survival benefit as compared to conventionally fractionated radiotherapy among patients with locally advanced unresectable PDAC. 25 Stereotactic body has several theoretical advantages over EBRT worth highlighting. Stereotactic body delivers higher doses of radiation administered over a smaller number of fractions, with improved tumor localization.…”
Section: Discussionmentioning
confidence: 99%